2019
DOI: 10.1017/pab.2019.24
|View full text |Cite
|
Sign up to set email alerts
|

Early Paleocene tropical forest from the Ojo Alamo Sandstone, San Juan Basin, New Mexico, USA

Abstract: Earliest Paleocene megafloras from North America are hypothesized to be low diversity and dominated by long-lived cosmopolitan species following the Cretaceous/Paleogene (K/Pg) mass extinction. However, megafloras used to develop this hypothesis are from the Northern Great Plains (NGP) of North America, and relatively little is known about floras from southern basins. Here, we present a quantitative analysis of an earliest Paleocene megaflora (<350 kyr after K/Pg boundary) from the Ojo Alamo Sandstone in th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
22
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 24 publications
(23 citation statements)
references
References 85 publications
(246 reference statements)
1
22
0
Order By: Relevance
“…The distribution of MA values has been shown to vary between environmental and climatic regimes, and previous studies have demonstrated that MA distribution in fossil floras reflects these modern distributions in expected ways (Flynn and Peppe, 2019;Lowe et al, 2018;Peppe et al, 2018;Royer et al, 2010). The distribution of Florissant MA values is centered at higher values relative to various wet temperate sites and is lacking leaves with the extremely high MA values found in typical wet tropical sites (Fig.…”
Section: Sclerophyllymentioning
confidence: 80%
“…The distribution of MA values has been shown to vary between environmental and climatic regimes, and previous studies have demonstrated that MA distribution in fossil floras reflects these modern distributions in expected ways (Flynn and Peppe, 2019;Lowe et al, 2018;Peppe et al, 2018;Royer et al, 2010). The distribution of Florissant MA values is centered at higher values relative to various wet temperate sites and is lacking leaves with the extremely high MA values found in typical wet tropical sites (Fig.…”
Section: Sclerophyllymentioning
confidence: 80%
“…Our results suggest that the rich Cenozoic macrofloras of Patagonia also carry a legacy of rich Cretaceous floras, as well as significantly earlier recovery of Paleocene species richness resulting from the persistence of most higher taxonomic levels (Supplementary Tables 1, 2). Nonetheless, an emerging body of research shows that floral diversity in the early Paleocene of the Denver and San Juan Basins can be higher relative to the more northerly WB (Johnson and Ellis 2002; Flynn and Peppe 2019; Lyson et al 2019). These studies show heterogeneity in NAM floral richness during the early Paleocene, a pattern warranting further intensive study.…”
Section: Discussionmentioning
confidence: 99%
“…1D) (Clyde et al 2014). While acknowledging work on diverse Paleocene floras from the more southerly Denver and San Juan basins (Johnson and Ellis 2002; Flynn and Peppe 2019; Lyson et al 2019), we focus on the floras of the WB for comparison, because they come from similar absolute paleolatitudes to our samples (i.e., ca. 51.3°S for the Danian Patagonian floras, ca.…”
Section: Methodsmentioning
confidence: 99%
“…Silicified stumps, wood fragments, and logs as much as 34 m long are common in the sandstones of the Ojo Alamo Sandstone. Leaf fossils are present but uncommon in the formation's claystones (Flynn and Peppe, 2019).…”
Section: Ojo Alamo Sandstonementioning
confidence: 99%
“…The overbank floodplain facies association contains sandy mudstones with interbedded fine-grained sandstones. This facies association's laterally discontinuous sand lenses, organic-rich fossil hash layers, and leaf fossils (Flynn et al, 2014;Flynn and Peppe, 2019) suggest deposition in fluvial floodplain environments (Kraus and Gwinn, 1997;Alexander and Fielding, 2006). Paleosols are uncommon; where present, they lack horizonation and are identified based solely on root traces.…”
Section: Overbank Floodplain Depositsmentioning
confidence: 99%